Time to revisit combination loop and thiazide diuretic therapy for patients with acute heart failure. (30th December 2022) - Zakeri, Rosita; Wilson, David G; Mohammed, Selma F
Graphical Abstract: Graphical Abstract A roadmap for integrated evaluation of diuretic strategies in acute heart failure. 6MWD, 6-minute walk distance; CPET, cardiopulmonary exercise testing; IVC, inferior vena cava; JVP, jugular venous pressure; NT-proBNP, N-terminal pro B-type natriuretic peptide; PCV, packed cell volume. Proposed metrics of diuretic response are further discussed in ter Maaten et al . 11